2013
DOI: 10.1002/grl.50905
|View full text |Cite
|
Sign up to set email alerts
|

Scale dependence and frontal formation of nighttime medium‐scale traveling ionospheric disturbances

Abstract: [1] Scale dependence of nighttime medium-scale traveling ionospheric disturbances (MSTIDs) is studied with the midlatitude ionosphere electrodynamics coupling model by changing initial perturbation scales. It is shown that both sporadic E (E s ) layer and Perkins instabilities have the scale dependence that a shorter wavelength mode tends to stop growing within a shorter period, whereas a very long wavelength mode grows so slowly in the E region that it does not effectively seed the Perkins instability in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…However, it was shown that the electrodynamic coupling processes between the E and F layers may lead to faster development of instability (Tsunoda 2006). Recently performed three-dimensional numerical modeling, which includes the E-F coupling process with dipole magnetic field lines, reproduces the main features of the nighttime mid-latitude MSTIDs (Yokoyama and Hysell 2010;Yokoyama 2013).…”
Section: Resultsmentioning
confidence: 99%
“…However, it was shown that the electrodynamic coupling processes between the E and F layers may lead to faster development of instability (Tsunoda 2006). Recently performed three-dimensional numerical modeling, which includes the E-F coupling process with dipole magnetic field lines, reproduces the main features of the nighttime mid-latitude MSTIDs (Yokoyama and Hysell 2010;Yokoyama 2013).…”
Section: Resultsmentioning
confidence: 99%
“…We would think that large perturbations will occur at locations where the post-sunset pre-reversal enhancements of vertical drift velocity are higher so that the global s/l distributions of irregularity occurrences can be readily explained. As for electrodynamic perturbations to become seeds of an instability process, numerical simulation by Yokoyama (2013) has shown that random electrodynamic perturbations without specific scale size will excite an instability process in the mid-latitude E-F region to result in medium-scale traveling disturbances with a size of 100 to 200 km. Whether a similar process will occur in the equatorial region needs to be studied further.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the Hall polarization electric fields occurring within the sporadic E layer instabilities might provide a mutual feedback to the polarization electric field generated in the Perkins process in the F region ionosphere. As a result of such feedback mechanism, the growth rate is predicted to increase, enabling the formation of instability within reasonable duration (Yokoyama, , ; Yokoyama et al, ; Yokoyama & Hysell, ). Experimental observations appear to provide credence to such theories (Chen et al, ; Kelley et al, ; Otsuka et al, , ; Saito et al, ).…”
Section: Introductionmentioning
confidence: 99%